Effect of fermentation temperature on the non-volatile components and in vitro hypoglycemic activity of Jinxuan black tea - Li, Guangneng; Zhang, Jianyong; Cui, Hongchun; Gao, Ying; Niu, Debao; Yin, Junfeng (Frontiers in Nutrition, 2024)
Fermentation significantly influences the chemical composition of black tea, yet the effects of different fermentation temperatures on non-volatile components and their in vitro hypoglycemic activity are insufficiently studied. This research investigates how varying temperatures (20°C, 25°C, 30°C) affect the bioactive profile and the inhibitory activity of Jinxuan black tea against α-glucosidase and α-amylase.Our results show that lower fermentation temperatures (20°C) lead to elevated levels of key bioactive compounds, including tea polyphenols (9.24%), soluble sugars (8.24%), thearubigins (7.17%), and theasinesin A (0.15%). These compounds correlate strongly with enhanced α-glucosidase inhibition (R = 0.76-0.97).Non-targeted metabolomic analysis revealed that 36 differential metabolites, including catechins, exhibited altered levels with increasing fermentation temperature.Notably, tea fermented at 20°C exhibited superior hypoglycemic activity, with α-glucosidase inhibition (IC50 = 14.00 ± 1.00 μg/mL) significantly outperforming α-amylase inhibition (IC50 = 2.48 ± 0.28 mg/mL). The findings of this research underscore the importance of fermentation temperature in optimizing the bioactive profile of black tea. It is proposed that recommendations for future processing or formulation should emphasize the use of lower fermentation temperatures, aimed at augmenting the health benefits linked to higher polyphenol content and stronger hypoglycemic activity.